2022
DOI: 10.1097/pgp.0000000000000910
|View full text |Cite
|
Sign up to set email alerts
|

Composite FOXL2 Mutation-positive Adult Granulosa Cell Tumor and Serous Borderline Tumor of the Ovary

Abstract: We report a case of a cystic ovarian neoplasm in a 76-yr-old female composed of 2 distinct and intimately associated components: a macrocystic adult granulosa cell tumor (AGCT) and a serous borderline tumor. The granulosa cell nature of the tumor was confirmed with positive immunohistochemical staining for inhibin, calretinin, and WT1, while the neoplastic nature of the granulosa cell proliferation was supported by the presence of a point mutation of the FOXL2 gene. A review of 19 previously reported mixed AGC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Previous studies by the applicant have suggested that estrogen regulates FOXL2 to promote apoptosis in human ovarian granulosa cell tumors (Rosario et al 2014, Wu et al 2019a). Mutations in the FOXL2 gene have been found in 95-97% of adult ovarian granulosa cell tumor patients, making FOXL2 gene mutation an important focus of research in ovarian granulosa cell tumors (Guerrieri et al 2023, Singh et al 2014, Yanagida et al 2017). To date, research has mainly focused on FOXL2 as a transcription factor regulating its downstream target genes, while relatively ignoring its own transcription and translation regulation (Caburet et al 2012, Fuller et al 2022, Tucker 2022, which is a limitation in FOXL2 research.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies by the applicant have suggested that estrogen regulates FOXL2 to promote apoptosis in human ovarian granulosa cell tumors (Rosario et al 2014, Wu et al 2019a). Mutations in the FOXL2 gene have been found in 95-97% of adult ovarian granulosa cell tumor patients, making FOXL2 gene mutation an important focus of research in ovarian granulosa cell tumors (Guerrieri et al 2023, Singh et al 2014, Yanagida et al 2017). To date, research has mainly focused on FOXL2 as a transcription factor regulating its downstream target genes, while relatively ignoring its own transcription and translation regulation (Caburet et al 2012, Fuller et al 2022, Tucker 2022, which is a limitation in FOXL2 research.…”
Section: Introductionmentioning
confidence: 99%